2017
DOI: 10.21804/20-1-1917
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal dialysis technique survival at Tygerberg Hospital in Cape Town, South Africa

Abstract: Background: The use of peritoneal dialysis (PD) as a treatment modality for patients with end-stage renal disease (ESRD) has been declining in many countries over the past few years. One of the reasons is technique failure, which occurs more frequently than is the case with chronic haemodialysis. Identifying and addressing the causes of technique failure is important in order to maintain more patients on PD, especially in settings where there are limited resources for chronic haemodialysis and a "PD first" app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 23 publications
2
3
3
Order By: Relevance
“…High mortality in the first 90 days following the start of RRT has been highlighted in studies conducted in other African countries [ 30–32 ]. The survival rates reported here are in line with the findings of two other South African studies that included the first 90 days following the initiation of treatment [ 19 , 33 ].…”
Section: Discussionsupporting
confidence: 89%
“…High mortality in the first 90 days following the start of RRT has been highlighted in studies conducted in other African countries [ 30–32 ]. The survival rates reported here are in line with the findings of two other South African studies that included the first 90 days following the initiation of treatment [ 19 , 33 ].…”
Section: Discussionsupporting
confidence: 89%
“…Patient survival in this cohort was similar to that reported by contemporaneous international series, but poorer than that reported in the local literature (Table 3). A greater proportion of patients with diabetes in the present cohort (29.2%) compared with previous local studies (Davidson et al [6] 9.8%, Isla et al [13] 9.9%, Kapembwa et al [7] 0.5%) and diverging survival outcomes for these patients, as observed in this study and reported by others, [17,18] may partially account for this discrepancy. Patients in our cohort were on average older (median age at PD initiation 44.3 years) than in contemporaneous local cohorts (Davidson et al [6] 39.7 years, Isla et al [13] 37.5 years, Kapembwa et al [7] 36 years).…”
Section: Discussioncontrasting
confidence: 61%
“…A greater proportion of patients with diabetes in the present cohort (29.2%) compared with previous local studies (Davidson et al [6] 9.8%, Isla et al [13] 9.9%, Kapembwa et al [7] 0.5%) and diverging survival outcomes for these patients, as observed in this study and reported by others, [17,18] may partially account for this discrepancy. Patients in our cohort were on average older (median age at PD initiation 44.3 years) than in contemporaneous local cohorts (Davidson et al [6] 39.7 years, Isla et al [13] 37.5 years, Kapembwa et al [7] 36 years). Older age, particularly in patients with diabetes, has been associated with increasing mortality risk on PD, [19] which may further explain the poorer overall survival in our series.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…Peritonitis is the leading cause of technique failure in patients on PD. [19][20][21] Peritonitis rates (0.82-0.87 events per patient-year), though still higher than the International Society for Peritoneal Dialysis recommendation of no more than 0.5 events per patient-year, have been declining steadily over the past 15 years. 12…”
Section: Peritoneal Dialysismentioning
confidence: 98%